Produtividade, teor e composição do óleo essencial de espécies de Mentha L. (Lamiaceae) cultivadas em hidroponia com variação de potássio - Garlet, Tanea Maria Bisognin (2007)
Hydropony is a promising cultivation technique to increase phytomass production and essential oil in mints. Thus, this study was carried out with Mentha arvensis L. fo. piperascens Holmes, Mentha x gracilis Sole and Mentha x piperita var. citrata (Ehrh.) Briq. aiming to evaluate the following: productivity, the content and the chemical composition of essential oil testing four potassium concentrations (276, 414, 552 and 690 mg L-1 of K) in the nutritive solution for each species; determine the content and the accumulation of nutrients on the three species and test the performance of the nutritive solution calculated for mint cultivation under the hydroponic NFT system. The maximum value of K concentrations in the hydroponic solutions negatively affects the growth and the accumulation of phytomass in the plants, but increases the essential oil content per plant. The suggested K concentrations for a good growth of the species are between 276 and 414 mg L-1. Each Mentha species has its oil rich in distinct metabolites and thus, according to the major desired component, the solution has to be chosen with the most adequate K content. The contents of essential oil and menthol in M. arvensis fo. piperascens increasing K concentration in the nutritive solution. The K dosis of 552 mg L-1 allows a higher oil yield in g plant-1, while the best chemical composition and and content of menthol is allowed by the K dosis of 690 mg L-1. Essential oil yield per plant and the linalool quantity in M. x gracilis are reduced with the maximum K dosis. The suggested K concentration for the obtention of better yield in M. x gracilis can not be higher than 276 mg L-1 in the nutritive solution. The total content and yield of essential oil per plant in M. x piperita var. citrata increase with the maximum K dosis, but in this dosis there is a decrease in the quantity of linalool and linalyl acetate. To increase essential oil yield per plant in M. x piperita var. citrata, associated to the accumulation of linalool and linalyl acetate, K concentrations between 414 and 552 mg L-1 are recommended. Regarding the mineral composition of the three Mentha species studied, it was observed that nitrogen, calcium and potassium are the macronutrients concentrated and extracted in higher quantities in all plant parts; following the same pattern, the micronutrients are iron, manganese and zinc. The greater macronutrients accumulations occur in the leaves, than in the stems and in minor quantities in the roots. For the cultivation of these three species under the hydroponic NFT system, the nutritive solution with 276 mg L-1 of K is quite efficient and assures a good phytomass production, preventing the plants to show any visual deficiency or toxicity signs. Therefore, the cultivation of mints under hydropony, associated to K variation, can be of utility for the obtention of excellent raw material , in small areas of cultivation, and become an important subsidy for new studies in Lamiaceae species, with economical and pharmacological potential.